Pemaknaan Iklan BMW i8 Roadster “Retirement is About Exploring Your Wide Open Future.” : Analisis Semiotika Roland Barthes - Siregar, Aina Nisa Fitria Pasha; Mardhiatillah, Athaya; Sherena, Aerika Ayu Sahara Putri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Advertising is a form of presenting and promoting the idea of a product or service that aims to help customers or viewers distinguish a product or service from others. On May 22, 2019 BMW released an advertisement with the title “Retirement is about exploring your wide open future.” which contains an appreciation of Dieter Zetsche who will retire as CEO of Mercedes Benz with a plot twist that keeps the audience entertained. This ad is unique because Mercedes Benz and BMW are leading companies that compete in the automotive sector, this makes this ad enjoyed by many viewers, up to 3 million viewers on Youtube within 6 days. In this study, we can understand the signs in advertisements and how myths can create meaning. The equivalent method of this research is qualitative with an interpretive approach and uses the semiotic theory of Roland Barthes. The results showed that the meaning of the signs in the advertisement